EXPRESSIVENESS IN THE STRUCTURE OF THE TEACHER'S LINGUISTIC PERSONALITY (A CASE STUDY OF K. D. USHINSKY) - Leonidovna Ariskina, Olga; Anatolyevna Dryangina, Elena (Revista Inclusiones, 2020)
The purpose of the present article is to analyze the linguistic personality of the educator K.D. Ushinsky as the author of the work "The Education of Man. Selected Writings", and to show that it is through the use of means of expression that the linguocognitive level of the linguistic personality (in particular, the value system) is revealed, and the implementation of communicative intentions is achieved, i.e. bringing the material to the reader in an accessible, bright, and influencing form.